A Novel Immunoassay for the Quantization of CYFRA 21–1 in Human Serum. Issue 4 (12th July 2013) - He, An; Liu, Tian‐Cai; Dong, Zhi‐Ning; Ren, Zhi‐Qi; Hou, Jing‐Yuan; Li, Ming; Wu, Ying‐Song
<x xml:space="preserve">Abstract</x> Background Cytokeratin 19 fragment antigen (CYFRA 21–1) is used to diagnose and monitor neoplasms. However, the main disadvantages of the currently available CYFRA 21–1 assays include heterogenous technology, being time‐consuming, and having low through‐put with low insensitivity. This study investigated the use of amplified luminescent proximity homogeneous immunoassay (AlphaLISA) for the quantization of CYFRA 21–1 in human serum. Methods The AlphaLISA kit was developed based on AlphaScreen detection technology with two different anti‐CYFRA 21–1 monoclonal antibodies. One was coated on AlphaLISA acceptor beads and the other was biotinylated. Donor beads were coated with streptavidin. The test conditions were optimized and analytical performance was studied. Results The measurement range of AlphaLISA CYFRA 21–1 kit was 0.08–500 ng/ml. Assay detection limit was 0.08 ng/ml. The intra‐ and interassay coefficients of variation were 3.00–9.00% and 4.00–10.00%, respectively. There was no cross‐reaction to alpha‐fetoprotein (AFP), carcinoembryonic antigen (CEA), neuron‐specific enolase (NSE), cancer antigen 19–9 (CA19–9), cytokeratins 8 (CK8), and cytokeratins 18 (CK18). The correlation coefficient of blood samples involved was 0.974 between CYFRA 21–1‐AlphaLISA assay and a commercial electrochemiluminescence immunoassay (ECLIA) CYFRA 21–1 kit (Roche). Conclusions The AlphaLISA CYFRA 21–1 kit developed in this study had favorable performance characteristics for clinical application with acceptable analytical sensitivity, specificity, and accuracy.